Immediate Maxillary Lateral Incisor Implants with Nonocclusal Loading Provisional Crowns - Miguel PenËœ arrocha, MD, DDS, PhD,1 Joana Lamas, DDS,2 Maria PenËœ arrocha, DDS, MD (Journal of Prosthodontics, 2008)
This clinical report series describes a treatment modality involving immediately placed dental implants in maxillary lateral incisor sites using noncemented immediate provisional crowns retained with calcinable copings (prosthetic complement used in preparing the metal for the definitive prosthesis).